PERAN LPTK DALAM PEMBENTUKAN TENAGA PROFESIONAL BERBASIS SYARIAT ISLAM DI ACEH - Muhibbuthabry Muhibbuthabry (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract: The Role of LPTK in Creating Syari’ah Based Professional Workforce in Aceh. The Institution of Learning for Educational workforce (LPTKs) plays an important role in the process of producing professionals in their fields. This article studies the extent to which such institutional programs play, especially those mainly associated with the Islamic sya’riah implemented in Aceh region. The writer of this article argues that, in terms of quality, it can be revealed from how far the lecturers are capable of facilitating the students’ learning process and its relevance to teaching materials. Therefore, the author concludes that the quality of learning can be conducted with the intensity of the systemic and synergistic lecturers, students, curriculum and learning materials, media, facilities, and learning systems in producing process and the optimal learning outcomes in accordance with the demands of curriculum.Kata Kunci: workforce, professional, LPTK, Aceh